Composite nanofiltration membrane as well as preparation method and application thereof

The composite nanofiltration membrane is prepared through layer-by-layer self-assembly technology, and the alternating coating of large-molecular and small-molecular-weight polyelectrolytes is used to solve the problem that the existing nanofiltration membrane is difficult to achieve both removal rate and permeability in micropollutant removal, achieving efficient micropollutant removal and high permeability, and the process is environmentally friendly.

CN119819134AActive Publication Date: 2025-04-15北京诺滤新材料科技有限公司 +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510014009.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-15
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

It is difficult for existing nanofiltration membranes to take into account high removal rate and high permeability during the removal of micropollutants, and the preparation process is not environmentally friendly.

Method used

A composite nanofiltration membrane is prepared by layer-by-layer self-assembly technology, and an alternating coating of large-molecular-weight and small-molecular-weight polyelectrolytes is formed to form a multi-layer film structure, adjusting the pore size and surface charge of the membrane to improve removal rate and permeability.

Benefits of technology

A high removal rate (over 90%) of micropollutants with molecular weight of about 200 Da is achieved, while maintaining high permeability, reducing the environmental impact of the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005229310320000111
    Figure BDA0005229310320000111
  • Figure BDA0005229310320000121
    Figure BDA0005229310320000121
  • Figure BDA0005229310320000131
    Figure BDA0005229310320000131
Patent Text Reader

Abstract

The invention provides a composite nanofiltration membrane as well as a preparation method and application thereof, and belongs to the technical field of pollutant removal. The surface of the macroporous base membrane is coated with a large-molecular-weight polyelectrolyte system to cover the macropores, and then the small-molecular-weight polyelectrolyte is used for filling the small pores of the base membrane, so that the rejection rate of the layer-by-layer self-assembled membrane on micropollutants can be improved, and relatively high permeability is kept while the pore diameter is reduced. Polyelectrolyte systems with different molecular weights are coated on the base membrane with high porosity, the multilayer composite nanofiltration membrane can be prepared by repeatedly coating, the removal rate of the prepared composite nanofiltration membrane on micropollutants with the molecular weight of about 200Da is more than 90%, and the removal rate is up to 99.8%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of pollutant removal, and in particular to a composite nanofiltration membrane and a preparation method and application thereof. Background Art

[0002] Micropollutants (MPs) usually refer to small organic molecules with a molecular weight between 200-1000Da. They are new pollutants composed of a large number of man-made and natural substances. They come from waste generated by industries such as industry, medicine and agriculture, such as medicines, pesticides, endocrine disruptors, plasticizers, cosmetics and other organic pollutants. They are characterized by their presence in trace amounts in water bodies, bioaccumulation and environmental toxicity, and serious harm to human health. In recent years, the content of micropollutants in groundwater, surface water and even drinking water has been increasing, with concentrations of several ng L -1 to μg L -1 Between, and has threatened the aquatic environment and drinking water quality, it has attracted great attention and attention worldwide. Many organic micropollutants have been listed in the EU's sewage discharge detection standards. Therefore, removing micropollutants from surface water and drinking water is an urgent task.

[0003] At present, the treatment technologies for micropollutants include: adsorption, advanced oxidation (AOPs) and membrane separation technology. The adsorption material is mainly activated carbon, which has low cost, high flexibility and is economical and practical; however, the adsorption efficiency of activated carbon is low, and a relatively high carbon dosage (up to 20 mg / L) is required to effectively remove micropollutants; in addition, due to the small size of micropollutants, the removal of micropollutants is generally low (<90%). After adsorption saturation, activated carbon becomes solid waste, which is a transfer from liquid pollutants to solid pollutants, and still requires further deep treatment. Advanced oxidation methods (AOPs) include three main technologies: (1) Ozonation technology; it is a mature and effective method for degrading most pharmaceuticals and industrial chemicals, and has been widely used in the existing water treatment industry; but O3 has certain selectivity and is difficult to degrade ozone-resistant micropollutants such as ibuprofen, which has certain limitations. (2) Fenton oxidation technology: The main material of Fenton oxidation reagent is iron, and it does not contain toxic substances. It is relatively environmentally friendly, green, and harmless to the environment. In order to avoid iron precipitation at a higher pH value during the Fenton oxidation process, it is usually required to be used in a low pH environment, and has certain requirements on the water quality of wastewater, so it is not suitable for large-scale application. Ultraviolet photolysis technology: For micropollutants that are easily decomposed by light, ultraviolet photolysis technology can better achieve the purpose of removal. However, this technology is not suitable for treating large-scale wastewater, and the removal efficiency is low.

[0004] Membrane separation technology is a low-energy, high-efficiency separation technology. Compared with traditional separation technologies (such as distillation, crystallization, extraction, chromatography, etc.), membrane separation technology is more sustainable and usually has lower costs. Therefore, in recent years, membrane separation technology has gradually become more important. Commercial reverse osmosis (RO) membranes can remove more than 90% of micropollutants, but due to the low water permeability of these membranes (1-2L / (m 2·h·bar)), making the reverse osmosis membrane process very energy-intensive. Compared to reverse osmosis membranes, commercial nanofiltration (NF) membranes have slightly larger pore sizes and higher water permeability coefficients, but this also results in a lower retention rate for micropollutants, especially for small molecules and uncharged micropollutants. In addition, reverse osmosis membranes and dense nanofiltration membranes were originally designed for desalination. When removing micropollutants, divalent and monovalent ions are removed together, resulting in a high-salt concentrate that is difficult to handle. In addition, the permeate also requires additional, re-added salt to make the produced water suitable for agricultural irrigation or human consumption. Therefore, commercial reverse osmosis membranes or dense nanofiltration membranes are not the best way to remove micropollutants.

[0005] In summary, it is currently believed that it is necessary to study nanofiltration membranes with appropriate pore sizes for the removal of micropollutants, so as to effectively remove micropollutants and allow inorganic salt ions to pass through the membrane to achieve good separation. How to accurately control the pore size of nanofiltration membranes, layer-by-layer self-assembly technology provides a good direction. In contrast to RO membranes, layer-by-layer self-assembled membranes allow monovalent salt ions such as sodium chloride to pass through, maintain high water flux, and the required operating pressure and energy are greatly reduced. By adjusting the pore size, surface charge and assembly materials of the layer-by-layer self-assembled membrane, separation design can be carried out for specific substances, and even the purposes of pollution resistance and antibacterial can be achieved. Layer-by-layer self-assembled nanofiltration (LBLNF) membrane is a separation membrane self-assembled by polyanion and cation electrolytes in a certain inorganic electrolyte aqueous solution background. From a microscopic perspective, the first factor that determines the pore size of the LBL membrane is the average distance between the adjacent two anion and cation pairs (or physical crosslinking) in the polyelectrolyte complex Pol+Pol-. The membrane pores are the interconnected gaps between the physical crosslinking points inside the polyelectrolyte multilayer membrane. It is generally believed that the LBL membrane coating process is divided into two stages: the first stage is the pore filling stage, in which the polyelectrolyte contacts the base membrane and fills the base membrane pores; the second stage is the layer growth stage, in which the polyelectrolyte fills the base membrane pores and then coats the base membrane surface. Therefore, the pore structure and chemical structure of the support membrane surface have a significant impact on the permeation separation performance of the LBL nanofiltration membrane. The base membrane pore size used in the currently disclosed patents is 10kDa-100kDa, and they are all small-pore membranes. For example, patent CN 107519765 A uses a PES ultrafiltration membrane with a molecular weight cutoff of 10kDa to prepare a polydopamine amphoteric composite nanofiltration membrane. The resulting membrane has a pure water permeability coefficient of 15.665LMH / bar and a molecular weight cutoff of 935Da. The maximum retention rate for drugs and personal care products (PPCP) is 92.50%. Patent CN 102553461 A prepares an inorganic / organic composite nanofiltration membrane on a base membrane with a molecular weight cutoff of 10 to 100 kDa. The transition layer is coated with a polyelectrolyte, and an inorganic soluble calcium salt and a soluble carbonate composite layer are formed on the surface of the transition layer. The composite nanofiltration membrane has a MgSO4 rejection rate of 76.5% to 95.5% and a low water flux of 1.7 to 5.3 LMH / bar by coating a polyelectrolyte on the transition layer and cross-linking to form a dense layer. Patent CN 113413760A performs a polyelectrolyte coating on an allyl modified polyethersulfone and sulfonated polyethersulfone blended ultrafiltration membrane with a molecular weight cutoff of 65 kDa. The resulting nanofiltration membrane has a MgSO4 rejection rate of 92% and a water flux of 7.4 LMH / bar. Patent CN 111659268 A uses a graphene-modified polyethersulfone hollow fiber ultrafiltration membrane with a molecular weight cutoff of 50 kDa, which is coated with polyacrylammonium chloride and sodium polystyrene sulfonate, and then cross-linked to obtain a nanofiltration membrane with a MgSO4 retention rate of 91%.Patent CN 102580550B uses a polysulfone ultrafiltration membrane with a molecular weight cutoff of 50 kDa to coat polycationic polydimethyldiallyl ammonium chloride and polyanionic polystyrene sodium sulfonate. The resulting nanofiltration membrane has a Na2SO4 rejection rate of 91% and a permeability coefficient of 5.1 LMH / bar. Patent CN 106310975 A selects a hollow fiber ultrafiltration membrane with a molecular weight cutoff of 50 kDa to prepare a polyelectrolyte multilayer nanofiltration membrane, and the MgSO4 rejection rate is 76% to 79%. However, the above LBL membranes cannot simultaneously achieve high permeability and separation performance.

[0006] In addition, many patents have been used to remove micropollutants using LBL membranes. Patent CN 105169962 B coated polyethyleneimine and graphene oxide, and the pure water flux of the prepared nanofiltration membrane was 6.97-22.96LMH / bar, and the retention rate of Bengal rose red dye was 80.46%-99.99%. Patent CN 110869108B used poly(diallyldimethylammonium chloride)-co-sulfone and poly(styrene sulfonate) to prepare layer-by-layer self-assembled nanofiltration membrane, and its water flux reached 9.4LMH / bar, MgCl2 retention rate was 97.1%, MgSO4 retention rate was 97.7%, Na2SO4 retention rate was 90.6%, micropollutant atenolol retention rate was 98.2%, naproxen retention rate was 59.9%, sulfamethoxazole retention rate was 33.1%, and bisphenol A retention rate was 30.3%. Patent CN 107519765 A coated polyethersulfone ultrafiltration membrane with polycation 2-hydroxypropyltrimethylammonium chloride chitosan and polyanion dopamine, and cross-linked with epichlorohydrin to obtain a composite nanofiltration membrane, which has a pure water permeability coefficient of 1.6LMH / bar and a retention rate of 92.50 for micropollutant carbamazepine. However, both cannot take into account membrane permeability and micropollutant removal rate at the same time. Summary of the invention

[0007] The purpose of the present invention is to provide a composite nanofiltration membrane and a preparation method and application thereof. The composite nanofiltration membrane material prepared by green and controllable layer-by-layer self-assembly technology has high removal rate and high permeability when removing micropollutants, solving the problem that the existing nanofiltration membrane is difficult to achieve both removal rate and permeability in the process of micropollutant removal and the preparation process is not green.

[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0009] The present invention provides a method for preparing a composite nanofiltration membrane, comprising the following steps:

[0010] Using the dip coating method,

[0011] (1) Alternately coating high molecular weight polyelectrolyte solutions with opposite charges on a base film, and repeating the alternate coating to a desired number of layers to obtain a macroporous filled polyelectrolyte multilayer film;

[0012] (2) alternately coating small molecular weight polyelectrolyte solutions with opposite charges on the macroporous filling polyelectrolyte multilayer membrane, and repeating the alternate coating until a desired number of polyelectrolyte multilayer membranes are formed to obtain a composite nanofiltration membrane;

[0013] The molecular weight of the high molecular weight polyelectrolyte in the high molecular weight polyelectrolyte solution is 200 to 3000 kDa;

[0014] The molecular weight of the small molecular weight polyelectrolyte in the small molecular weight polyelectrolyte solution is 1 to 200 kDa.

[0015] Preferably, the porosity of the base membrane is 50-80%, and the pore size is 10-200 nm; the material of the base membrane includes polyethersulfone, polyacrylonitrile, polysulfone, polyetheretherketone, polyimide or polyvinyl chloride, and the type of the base membrane is a hollow fiber membrane.

[0016] Preferably, the high molecular weight polyelectrolyte and the low molecular weight polyelectrolyte independently include polycation electrolytes or polyanion electrolytes.

[0017] Preferably, the polycationic electrolyte comprises one or more of polyacrylamine hydrochloride, polydimethyldiallylammonium chloride, polyethyleneimine and polyethyleneamine;

[0018] The polyanion electrolyte includes one or more of sodium polystyrene sulfonate, sodium polyacrylate, sodium polyvinyl sulfonate and sulfonated polyetheretherketone.

[0019] Preferably, the concentration of polyelectrolyte in the high molecular weight polyelectrolyte solution and the low molecular weight polyelectrolyte solution is 0.01-10 g / L.

[0020] Preferably, the salt in the background salt solution used for the high molecular weight polyelectrolyte solution and the low molecular weight polyelectrolyte solution independently includes NaF, NaCl, NaBr or NaNO3, and the salt concentration in the background salt solution is 0.0001-2.5 mol / L.

[0021] Preferably, based on obtaining one bilayer by alternating coating once, the number of layers of alternating coating in step (1) is 2 to 10 bilayers; and the number of layers of alternating coating in step (2) is 1 to 10 bilayers.

[0022] Preferably, the order of alternating coating in step (1) and step (2) is independent of coating the polycationic electrolyte and the polyanionic electrolyte in sequence.

[0023] The present invention provides a composite nanofiltration membrane prepared by the preparation method described in the above technical solution.

[0024] The present invention provides application of the composite nanofiltration membrane described in the above technical solution in the treatment of drinking water or surface water.

[0025] The invention provides a preparation method of a composite nanofiltration membrane. The invention adopts layer-by-layer self-assembly dip coating technology, firstly adopts a high molecular weight polyelectrolyte system to alternately coat the surface of a high-porosity base membrane to cover and fill the large pores, and then alternately coats a low molecular weight polyelectrolyte to fill the small pores of the base membrane, which can improve the interception rate of the layer-by-layer self-assembly membrane for magnesium sulfate, reduce the pore size while maintaining a high permeability, and can achieve high permeability while obtaining a high micro-pollutant removal rate, so as to obtain a composite nanofiltration membrane with high permeability and high micro-pollutant removal rate. The prepared composite nanofiltration membrane has a removal rate of more than 90% for micro-pollutants with a molecular weight of about 200Da, and the removal rate is as high as 99.8%.

[0026] The present invention adopts layer-by-layer self-assembly technology to prepare multilayer composite nanofiltration membranes. The process is simple, efficient, highly controllable, green and environmentally friendly (using non-toxic and harmless water as a solvent), low-cost, and automated. By adjusting the parameters, methods, and assembly materials of the membrane coating process, the pore size and surface characteristics of the membrane can be more accurately controlled, thereby improving the overall performance and service life of the membrane.

[0027] The separation performance of the composite nanofiltration membrane material obtained by the present invention is suitable for the removal of micropollutants of different molecular weights. The nanofiltration membrane prepared by using polyelectrolyte coatings of different molecular weights significantly improves the removal efficiency of micropollutants. Specifically, the low molecular weight polyelectrolyte coating can form a dense membrane structure and enhance the interception capacity of small molecular weight micropollutants; while the high molecular weight polyelectrolyte coating provides higher permeability and is suitable for removing micropollutants of larger molecular weight.

[0028] The composite nanofiltration membrane material prepared by the present invention is suitable for removing micropollutants of different properties. The combined use of polyelectrolytes of different molecular weights can optimize the physicochemical properties of the membrane, such as hydrophilicity and surface charge, thereby achieving efficient removal of a variety of micropollutants. The method not only improves the selectivity and stability of the nanofiltration membrane, but also exhibits excellent durability and mechanical properties under complex water quality conditions, and is suitable for a variety of water treatment applications.

[0029] The nanofiltration membrane prepared by the present invention has excellent osmotic separation performance, a permeability coefficient between 10 and 30 LMH / bar, and a removal rate of micropollutants with a molecular weight of less than 200 Da in drinking water or surface water that is stable between 90.0 and 99.8%. The removal rate and permeability of the membrane for micropollutants are much higher than those of existing commercial nanofiltration membranes. DETAILED DESCRIPTION

[0030] In the present invention, unless otherwise specified, the raw materials or reagents used are commercially available products well known in the art.

[0031] The present invention provides a method for preparing a composite nanofiltration membrane, comprising the following steps:

[0032] Using the dip coating method,

[0033] (1) Alternately coating high molecular weight polyelectrolyte solutions with opposite charges on a base film, and repeating the alternate coating to a desired number of layers to obtain a macroporous filled polyelectrolyte multilayer film;

[0034] (2) alternately coating small molecular weight polyelectrolyte solutions with opposite charges on the macroporous filling polyelectrolyte multilayer membrane, and repeating the alternate coating until a desired number of polyelectrolyte multilayer membranes are formed to obtain a composite nanofiltration membrane;

[0035] The molecular weight of the high molecular weight polyelectrolyte in the high molecular weight polyelectrolyte solution is 200 to 3000 kDa;

[0036] The molecular weight of the small molecular weight polyelectrolyte in the small molecular weight polyelectrolyte solution is 1 to 200 kDa.

[0037] The present invention has no particular limitation on the specific operation of the dip coating method, and the method can be self-assembled layer by layer according to coating methods well known in the art.

[0038] In the present invention, the polyelectrolyte solution with opposite charges is a positively charged polycation electrolyte solution and a negatively charged polyanion electrolyte solution. The polyelectrolyte solution is obtained by dissolving the polyelectrolytes with opposite charges in a background salt solution.

[0039] The coating method of the present invention is a dip-coating method, that is, the base film is first immersed in a polycation electrolyte solution for 5 to 30 minutes, then immersed in a background salt solution without polycation electrolyte to wash away unbound polycations, then transferred to a polyanion electrolyte solution and immersed for 5 to 30 minutes, and then washed in a background salt solution without polyanion electrolyte, and a polyelectrolyte double layer is completed. The present invention first alternately coats a plurality of layers of a large molecular weight polycation electrolyte and a polyanion electrolyte to fill the large pores of the base film, and repeats the large molecular weight coating step to the required number of layers; then alternately coats a plurality of layers of a small molecular weight polycation electrolyte and a polyanion electrolyte to cover the small pores, and repeats the small molecular weight polyelectrolyte coating step to the required number of layers, until a polyelectrolyte multilayer film of a desired thickness is formed.

[0040] In the present invention, the porosity of the base membrane is preferably 50-80%, more preferably 55-60%, and the pore size is preferably 10-200 nm, more preferably 14-90 nm; the material of the base membrane includes polyethersulfone, polyacrylonitrile, polysulfone, polyetheretherketone, polyimide or polyvinyl chloride, and the type of the base membrane is preferably a hollow fiber membrane. In the present invention, the molecular weight cutoff of the base membrane is preferably 110-350 kDa, more preferably 120-280 kDa. The nanofiltration membrane formed by the macroporous base membrane of the present invention has a smaller pore size, which enhances the size screening effect of the membrane and can achieve a higher micro-pollutant removal rate.

[0041] In the present invention, the molecular weight of the large molecular weight polyelectrolyte in the large molecular weight polyelectrolyte solution is 200-3000 kDa, preferably 600-1000 kDa; the molecular weight of the small molecular weight polyelectrolyte in the small molecular weight polyelectrolyte solution is 1-200 kDa, preferably 1.5-100 kDa, more preferably 15-70 kDa.

[0042] In the present invention, the molecular weight of the polyelectrolyte has a significant effect on the assembly, growth and performance of the multilayer film. First, the polyelectrolyte chains with higher molecular weight have a loose multilayer structure due to their larger volume and lower mobility, which leads to an increase in the permeability of the membrane, but the selectivity and retention performance may be reduced. On the contrary, the polyelectrolyte chains with lower molecular weight have higher mobility and can be more closely combined to form a denser multilayer structure. This compactness helps to improve the selectivity and retention performance of the membrane, but may reduce its permeability. During the assembly process, low molecular weight polyelectrolyte chains are more likely to be evenly distributed on the substrate surface to form a smooth coating, while high molecular weight polyelectrolyte chains may cause the coating surface roughness to increase. In addition, the molecular weight also affects the mechanical properties and stability of the multilayer film. Low molecular weight polyelectrolyte multilayer films generally have higher mechanical strength and chemical stability, while high molecular weight polyelectrolyte multilayer films may be more flexible. In summary, the molecular weight of the polyelectrolyte significantly affects the assembly, growth and final performance of the multilayer film by affecting the mobility, binding tightness and surface characteristics of the chain. The present invention selects a suitable high molecular weight polyelectrolyte as a pore-filling bottom layer and a suitable low molecular weight polyelectrolyte as a dense top layer according to the porosity and pore size of the base film.

[0043] In the present invention, the large molecular weight polyelectrolyte and the small molecular weight polyelectrolyte independently include polycation electrolytes or polyanion electrolytes.

[0044] In the present invention, the polycationic electrolyte preferably includes one or more of polyacrylamine hydrochloride (PAH), polydimethyldiallyl ammonium chloride (PDADMAC), polyethyleneimine (PEI) and polyvinylamine (PVAm); the polyanionic electrolyte preferably includes one or more of sodium polystyrene sulfonate (PSS), sodium polyacrylate (PAA), sodium polyvinyl sulfonate (PVS) and sulfonated polyetheretherketone.

[0045] In the present invention, the concentration of polyelectrolyte in the high molecular weight polyelectrolyte solution and the low molecular weight polyelectrolyte solution is 0.01 to 10 g / L, more preferably 0.05 to 5 g / L, and even more preferably 0.1 g / L.

[0046] The concentration of polyelectrolyte has little effect on the pore size of the nanofiltration membrane, but it will affect its permeability. When polycations and polyanions contact and combine with each other, aggregates will form in the pores and on the surface of the porous base membrane. The aggregates are evenly dispersed in the membrane and on the surface. Excessive aggregates will hinder the subsequent coating polyelectrolyte from entering the membrane and adsorbing on the membrane surface. The higher the polyelectrolyte concentration, the thicker the coating will usually be, because high-concentration polyelectrolyte solutions contain more polymer chains, which can form a thicker coating on the surface of the base membrane. Thicker coatings will increase the resistance of the solution to pass through the membrane, causing the permeability coefficient of the nanofiltration membrane to decrease. Too low a polyelectrolyte concentration will cause the membrane pores to be unable to be completely filled, resulting in defects and unevenness in the membrane, and inability to effectively remove micropollutants.

[0047] In the present invention, the salt in the background salt solution used for the high molecular weight polyelectrolyte solution and the low molecular weight polyelectrolyte solution independently includes NaF, NaCl, NaBr or NaNO3, and the salt concentration in the background salt solution is preferably 0.0001-2.5 mol / L, more preferably 0.01-1.0 mol / L, and further preferably 0.05 mol / L.

[0048] The present invention has no particular limitation on the preparation methods of the high molecular weight polyelectrolyte solution, the low molecular weight polyelectrolyte solution and the background salt solution. The corresponding solutions can be prepared according to methods well known in the art.

[0049] The polyelectrolyte is dispersed in the background salt solution. The type of background salt solution has a significant effect on the permeability selectivity of the nanofiltration membrane, which is mainly reflected in the coating thickness, uniformity, mechanical properties, permeability and stability. Different types of background salts will change the adsorption behavior of the polyelectrolyte and the arrangement of the molecular chains, thereby affecting the final performance of the coating. The specific effects brought about by different types of salt ions are due to the different positions of the ions in the Hofmeister sequence. The Hofmeister sequence describes the effect of ions on the solubility and stability of proteins and other macromolecules. The ions in the sequence are arranged from strong to weak according to their effect on the solubility of macromolecules, such as sulfate ions (SO4 2- ) usually stabilizes the structure of macromolecules, while thiocyanate ion (SCN - ) will destroy the structure of the macromolecule. The ions in the background salt will affect the conformation and adsorption behavior of the polymer chain through electrostatic interaction and solvation effect. The ions in the background salt will shield the charge on the polyelectrolyte molecular chain, reduce the electrostatic repulsion, and make it easier for the molecular chain to approach and adsorb on the substrate surface, thereby increasing the coating thickness. For example, when NaCl is used as the background salt, Cl - It will moderately shield the charge on the polycation chain, reduce the electrostatic repulsion, and make it easier for the polycation chain to approach and adsorb on the surface of the base film, so that the coating thickness may increase. 2- It has a strong solvation effect, which will significantly affect the arrangement of polymer chains, so that the coating thickness may be reduced, and the change in coating thickness will affect the permeability and selectivity of the nanofiltration membrane. The size and charge density of different salt ions will also affect the conformation of the polyelectrolyte chain and the degree of expansion of the adsorption layer, thereby changing the thickness and uniformity of the coating. In addition, the type of background salt will also affect the mechanical properties and stability of the coating. For example, Na2SO4 can improve the chemical stability and durability of the coating, while other salts such as NaCl may make the coating more flexible and easy to damage.

[0050] Furthermore, the concentration of the polyelectrolyte background salt solution significantly affects the conformation and growth mechanism of the polyelectrolyte multilayer during the assembly process. The mechanism of polyelectrolyte multilayer growth includes the following steps: First, the substrate surface carries an initial charge, which attracts polyelectrolyte molecules with opposite charges. With the adsorption of the first layer of polyelectrolyte, the surface charge reverses, attracting the second layer of polyelectrolyte molecules with opposite charges. This process is repeated continuously to form a multilayer structure. There is a competitive relationship between salt ions and polyelectrolytes: at low salt concentrations, adjacent groups with the same charge on the polyelectrolyte segments repel each other, resulting in a more stretched conformation of the segments. At this time, the oppositely charged groups on the anionic and cationic polyelectrolyte segments combine with each other, which is called internal compensation; at high salt concentrations, the charge of the polyelectrolyte is mainly neutralized by the oppositely charged salt ions, resulting in an electrostatic screening effect, at which time the repulsive force between adjacent groups with the same charge on the segments is weakened, resulting in a more agglomerated conformation of the segments; the combination of charged groups on the polyelectrolyte segments and salt ions is called external compensation. It is generally believed that when internal compensation is dominant, the membrane thickness is smaller and the membrane is denser; when external compensation is dominant, the membrane is relatively thicker, more open and loose. The background salt concentration affects the adsorption efficiency of each layer and the performance of the final membrane by adjusting the electrostatic shielding effect and the flexibility of the polyelectrolyte chain. As the background salt concentration increases, the electrostatic shielding effect between the polyelectrolyte chains is enhanced, making it easier for the molecular chains to approach and adsorb on the substrate surface, thereby forming a thicker coating. During the assembly process, the background salt concentration also affects the conformation and diffusion behavior of the polyelectrolyte chains. High-concentration salt solutions will cause the polyelectrolyte chains to be arranged more closely, forming a dense multilayer structure. The principle of polyelectrolyte coating is based on electrostatic interaction. The positively and negatively charged polyelectrolyte molecules form a stable multilayer structure through electrostatic attraction during the alternating deposition process; the deposition of each layer will affect the adsorption behavior of the next layer, thereby building the required membrane thickness and performance layer by layer.

[0051] In the present invention, based on the principle of obtaining one double layer by alternating coating at a time, the number of layers of alternating coating in step (1) is preferably 2 to 10 double layers, more preferably 4 to 8 double layers; the number of layers of alternating coating in step (2) is preferably 1 to 10 double layers, more preferably 4 to 8 double layers.

[0052] In the present invention, the number of polyelectrolyte coating layers has a great influence on the permeability selectivity of the nanofiltration membrane. The number of coating layers of high molecular weight polyelectrolyte must ensure that most of the large pores of the base membrane can be covered to ensure high flux, and the number of layers of low molecular weight polyelectrolyte must ensure that a complete dense cortex can be formed to ensure a high micro-pollutant removal rate of the nanofiltration membrane. In an embodiment of the present invention, at least 2 to 10 double layers of high molecular weight polyelectrolyte are coated, so that the large molecular weight polyelectrolyte fills the larger pores of the base membrane to ensure high flux, more preferably 3-6 double layers; at least 1 to 10 double layers of low molecular weight polyelectrolyte are coated, and the small molecular weight polyelectrolyte fills the smaller pores of the base membrane to ensure that the top layer is dense, thereby achieving high flux and high retention, more preferably 3-6 double layers.

[0053] In the present invention, the order of alternating coating in step (1) and step (2) is independent of sequentially coating the polycationic electrolyte and the polyanionic electrolyte.

[0054] The present invention provides a composite nanofiltration membrane prepared by the preparation method described in the above technical solution.

[0055] The present invention provides the application of the composite nanofiltration membrane described in the above technical solution in the treatment of drinking water or surface water. The present invention has no special limitation on the application method, and the application can be carried out according to methods well known in the art.

[0056] The dip coating method adopted in the present invention has a simple and direct process. It only needs to immerse the base membrane in the coating solution and then draw it out at a controllable speed. The coating automation can be achieved without complex equipment and professional skills. Since the equipment and operation are simple, automated, and the coating solution covers a wide range, the dip coating method is low in cost and suitable for large-scale production. The process has high repeatability and can achieve consistent coating quality and thickness, and is very suitable for large-scale nanofiltration membrane production. By adjusting the membrane filament pulling speed and the type and concentration of the background salt solution, the thickness of the coating can be accurately controlled to meet the application requirements of nanofiltration membranes under different situations. Compared with other coating technologies, the dip coating method does not involve irritating chemicals and high-energy consumption operations, and this method is more environmentally friendly and energy-saving.

[0057] The present invention has no particular limitation on the form and type of the composite nanofiltration membrane, and hollow fiber membranes, flat membranes, roll membranes, and tubular membranes known in the art can all be used. The method of the present invention is particularly suitable for the preparation of nanofiltration materials, which can be achieved by effectively regulating the parameters of the polyelectrolyte coating.

[0058] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0059] In the embodiments of the present invention, the nanofiltration membrane pure water permeability coefficient (P) refers to the definition of water flux in GB / T 34242-2017 "Nanofiltration Membrane Test Method". The nanofiltration membrane pure water permeability coefficient is defined as the amount of water permeating per unit membrane area per unit time per unit pressure under certain operating conditions.

[0060]

[0061] Where P represents the pure water permeability coefficient (L / m 2 hbar), Δm is the sample mass (kg), ρ is the density of water (kg / L), S is the effective membrane area (m 2 ), Δt is the sample connection time (h), and Δp is the transmembrane pressure (bar).

[0062] The test conditions for the permeability coefficient of the composite nanofiltration membrane prepared by the present invention are: deionized water is used as the feed liquid, the test pressure is 0.1-0.5 MPa, and the test system temperature is 25°C.

[0063] The micro-pollutant removal rate (R M ) Refer to the definition in "J.Membr.Sci.2018,549,120-128". Driven by the pressure gradient, the membrane material's preference or separation ability for specific micropollutants, that is, the ratio of the concentration of micropollutants on the permeate side to the concentration of micropollutants on the feed side. The micropollutant removal rate reflects the selectivity and separation efficiency of the nanofiltration membrane for micropollutants and is an important indicator for evaluating the performance of the nanofiltration membrane.

[0064] The detection of micropollutant content in water samples was carried out in accordance with the methods in "Technical Guidelines for Accuracy Assessment of New Pollutant Screening Liquid Chromatography-Mass Spectrometry (Trial)", "Anal.Chim.Acta 2017,959,91" and "Chemosphere2021,273,128524". The test steps are as follows: prepare a micropollutant feed solution with a concentration of 200μg / L, and take samples after constant pressure operation in the cross-flow NF device for 24 hours. The test pressure range is 3 to 6bar. The content of micropollutants in the feed solution sample and the NF membrane permeate sample is detected by high performance liquid chromatography-mass spectrometry.

[0065] Preparation of micropollutant solution: The micropollutant feed solution uses a mixed solution with a concentration of 200 μg / L for each micropollutant. The mother solution of each micropollutant (concentration of 1 g / L) is prepared by dissolving each type of micropollutant (see Table 1) in mass spectrometry grade methanol and stored in a brown reagent bottle. The mother solution is stored in a -8°C refrigerator. Pipette 0.2 mL of each micropollutant mother solution into the feed tank, dilute the transferred stock solution to 3 L with ultrapure water, and adjust the pH value to 5.8 to obtain a feed mixture with a concentration of 200 μg / L for each micropollutant.

[0066] Table 1 Molecular weight of micropollutants tested in the experiment

[0067]

[0068] Micropollutant experimental filtration conditions: filtration temperature is 25℃±3℃, test mode is cross-flow mode, solution concentration ensures constant concentration mode, flow rate is 0.66m / s, filtration pressure is 3-6bar, and filtration time is 24h.

[0069] Preparation of standard samples for micro-pollutant concentration test: Pipette an appropriate amount of 1g / L micro-pollutant mother solution for series concentration gradient dilution: 0, 10, 20, 50, 100, 200, 400μg / L, each concentration solution volume is 1mL, which is convenient for establishing the liquid phase mass spectrometry line. The concentration range covers the feed solution and permeate concentration in the filtration test.

[0070] Micropollutant concentration test conditions: The target analytes were analyzed by ultra-high performance liquid chromatography-triple quadrupole mass spectrometry (UHLC-TQ-MS 30A / Sciex quadrupole 5500, Waters, USA). An Agilent Poroshell 120EC-C18 (3.0×100 mm, 2.7 μm) column was used to separate and quantify the target analytes and their internal standards (ILISs). All target analytes and their internal standards were separated by a gradient method, and the optimized mobile phase composition was as follows: Milli-Q water with 0.1% formic acid (mobile phase A) and a 50:50 (v / v) mixture of methanol and acetonitrile with 0.1% formic acid (mobile phase B). The gradient program started with 10% mobile phase B, maintained isocratic for 1.5 minutes, and then increased to 90% mobile phase B at 15 minutes and maintained until 22 minutes. At the end of the chromatographic run, the column was re-equilibrated to the initial conditions within 0.5 minutes and stabilized for 3 minutes. The total mobile phase flow rate was 0.45 mL / min. The column temperature and autosampler temperature were maintained at room temperature (24 ± 2 and 6 °C), respectively. An injection volume of 10 μL was used for all analyses. A post-column switch was used to direct the first 1.35 mL of eluate, which may contain salts / weakly bound impurities, to waste and switched to tandem mass spectrometry analysis after 3.0 minutes. Tandem mass spectrometry analysis was performed on a triple quadrupole with iFunnel technology, which combines high-efficiency electron spray ionization (ESI). Tandem mass spectrometry analysis was performed in both positive ESI (+) and negative ESI (-) modes. Nitrogen was used as drying gas and collision gas. The optimal conditions of the mass spectrometry system were: drying gas temperature 200 °C; drying gas flow rate 14 L / min; nebulizer pressure 20 psi; sheath gas heater temperature 250 °C; sheath gas flow rate 11 L / min; nozzle voltage 1500 V; capillary voltage 3000 V; fragmentation voltage 380 V.

[0071] The removal rate of micropollutants by nanofiltration membrane is calculated by the following formula:

[0072]

[0073] Among them, R M Indicates the removal rate of micropollutants by the membrane, C f represents the concentration of micropollutants in the feed liquid, C p Indicates the concentration of micropollutants on the permeate side.

[0074] Example 1

[0075] A polyethersulfone hollow fiber membrane (obtained according to the prior art "Desalination.2024,574,117229") was selected as the base membrane (porosity 55%, pore size 14 nm, molecular weight cutoff MWCO = 120 kDa, inner diameter 0.72 mm, outer diameter 1.25 mm) for polyelectrolyte coating).

[0076] First, a large molecular weight polyanion sodium polystyrene sulfonate (PSS, Mw = 1,000 kDa, purchased from Anhui Cool Biotechnology Co., Ltd.) was dissolved in a 0.05 mol / L sodium chloride solution to prepare a 0.1 g / L PSS polyelectrolyte solution, and a small molecular weight polyanion sodium polystyrene sulfonate (Mw = 70 kDa, purchased from Anhui Cool Biotechnology Co., Ltd.) was dissolved in a 0.05 mol / L sodium chloride solution to prepare a 0.1 g / L PSS polyelectrolyte solution; then a large molecular weight polycation polydimethyldiallylammonium chloride (PDADMAC, Mw = 600 kDa, purchased from Shandong Youso Chemical Technology Co., Ltd.) was dissolved in a 0.05 mol / L sodium chloride solution to prepare a 0.1 g / L PDADMAC polyelectrolyte solution, and a small molecular weight polycation polyvinylamine (PVAm, Mw = 100 kDa, purchased from Wuhan Kemik Biomedical Technology Co., Ltd.) was dissolved in a 0.05 mol / L sodium chloride solution to prepare a 0.1 g / L PVAm polyelectrolyte solution;

[0077] Using a high molecular weight polycation PDADMAC (600 kDa) as the first layer, the above polyethersulfone-based membrane is immersed in a PDADMAC (600 kDa) solution for coating for 15 minutes and then washed with a 0.05 mol / L sodium chloride solution, then the membrane is immersed in a high molecular weight polyanion PSS (1000 kDa) solution for coating for 15 minutes and then washed with a 0.05 mol / L sodium chloride solution, that is, a polyelectrolyte double layer is completed, and the high molecular weight system coating steps are repeated until 4 PDADMAC / PSS (600 kDa / 1000 kDa) double layers are formed. The above membrane is further immersed in a low molecular weight polycation PVAm (100 kDa) solution for coating for 15 minutes and then washed with a 0.05 mol / L sodium chloride solution, then immersed in a low molecular weight polyanion PSS (70 kDa) solution for coating for 15 minutes and then washed with a 0.05 mol / L sodium chloride solution, and the low molecular weight system coating steps are repeated until 4 PVAm / PSS (100 kDa / 70 kDa) double layers are formed. The final composite nanofiltration membrane has 4 double layers of coating of the large molecular weight system PDADMAC / PSS (600kDa / 1000kDa) and 4 double layers of coating of the small molecular weight system PVAm / PSS (100kDa / 70kDa). After coating, glycerol is used for moisturizing and drying to obtain a composite nanofiltration membrane.

[0078] According to the above test method, the micro-pollutant removal rate test results are: the pure water permeability coefficient is 12.3L m -2 h - 1 bar -1 The removal rates of ibuprofen (Mw = 206 Da) were 98.6%, carbamazepine (Mw = 236 Da) were 99.5%, and atenolol (Mw = 266 Da) were 98.0%.

[0079] Example 2

[0080] The only difference from Example 1 is that the low molecular weight polycation is replaced with polyacrylamine hydrochloride (PAH, Mw = 15 kDa, purchased from Hubei Yamade Biopharmaceutical Co., Ltd.) and dissolved in 0.05 mol / L sodium chloride solution to prepare a 0.1 g / L polyelectrolyte solution. The high molecular weight polyelectrolyte system is also coated with 4 double layers, and the low molecular weight polyelectrolyte system is coated with 4 double layers. The remaining steps are the same as in Example 1.

[0081] The test results of micro-pollutant removal rate are as follows: the pure water permeability coefficient is 10.9L m -2 h -1 bar -1The removal rates of ibuprofen (Mw = 206 Da) were 95.4%, carbamazepine (Mw = 236 Da) were 98.7%, and atenolol (Mw = 266 Da) were 99.0%.

[0082] Example 3

[0083] The only difference from Example 1 is that the coating background salt is replaced by NaNO3 from NaCl in Example 1, 4 double layers of the coating high molecular weight PDADMAC / PSS system and 4 double layers of the coating low molecular weight PVAm / PSS system, for a total of 8 double layers.

[0084] The test results of micro-pollutant removal rate are as follows: the pure water permeability coefficient is 11.1Lm -2 h -1 bar -1 The removal rates of ibuprofen (Mw = 206 Da) were 98.9%, carbamazepine (Mw = 236 Da) were 99.5%, and atenolol (Mw = 266 Da) were 99.8%.

[0085] Example 4

[0086] The only difference from Example 1 is that the coating background salt is replaced by NaF from NaCl in Example 1, 4 double layers of the high molecular weight PDADMAC / PSS system and 4 double layers of the low molecular weight PVAm / PSS system are coated, for a total of 8 double layers.

[0087] The test results of micro-pollutant removal rate are as follows: the pure water permeability coefficient is 13.7L m -2 h -1 bar -1 , ibuprofen (Mw = 206Da) removal efficiency was 93.8%, carbamazepine (Mw = 236Da) removal efficiency was 94.5%, and atenolol (Mw = 266Da) removal efficiency was 95.0%. Examples 1, 3, and 4 show that the type of coating background salt can affect the performance of LBL membranes, with chaotropic anions (NO3 - ) as the background salt, the membrane prepared was denser and had higher retention of micropollutants, but lower flux.

[0088] Example 5

[0089] A polyethersulfone hollow fiber membrane (porosity of 60%, pore size of 90 nm, molecular weight cutoff MWCO = 280 kDa, inner diameter of 0.83 mm, outer diameter of 1.29 mm, obtained according to the prior art "Desalination.2023,557,116596") was selected as the base membrane for polyelectrolyte coating.

[0090] 0.1 g / L high molecular weight polyanion PSS (Mw = 1000 kDa, purchased from Anhui Cool Bioengineering Co., Ltd., 0.05 mol / L NaCl), 0.1 g / L low molecular weight polyanion PAA (Mw = 1.5 kDa, 0.05 mol / L NaCl), 0.1 g / L high molecular weight polycation PDADMAC (Mw = 600 kDa, purchased from Shandong Yousuo Chemical Technology Co., Ltd., 0.05 mol / L NaCl), 0.1 g / L low molecular weight polycation PAH (Mw = 15 kDa, purchased from Hubei Yamade Biotechnology Co., Ltd., 0.05 mol / L NaCl) were used.

[0091] Using a large molecular weight polycation PDADMAC (600kDa) as the first layer, the polyethersulfone-based membrane is immersed in a PDADMAC (600kDa) solution for coating for 15 minutes and then washed with a 0.05mol / LNaCl solution, and then the membrane is immersed in a large molecular weight polyanion PSS (1000kDa) solution for coating for 15 minutes and then washed with a 0.05mol / LNaCl solution, that is, a polyelectrolyte double layer is completed, and the large molecular weight system coating steps are repeated until 5 PDADMAC / PSS (600kDa / 1000kDa) double layers are formed. The above membrane is further immersed in a small molecular weight polycation PAH (15kDa) solution for coating for 15 minutes and then washed with a 0.05mol / L sodium chloride solution, and then immersed in a small molecular weight polyanion PAA (1.5kDa) solution for coating for 15 minutes and then washed with a 0.05mol / L sodium chloride solution. Repeat the coating steps of the low molecular weight system until 5 PAH / PAA (150 kDa / 1.5 kDa) double layers are formed. Finally, the high molecular weight system PDADMAC / PSS (600 kDa / 1000 kDa) coating has 5 double layers, and the low molecular weight system PAH / PAA (15 kDa / 1.5 kDa) coating has 5 double layers in the composite nanofiltration membrane.

[0092] The test results of micro-pollutant removal rate are as follows: the pure water permeability coefficient is 15.2L m -2 h -1 bar -1 The removal rates of ibuprofen (Mw = 206 Da) were 97.0%, carbamazepine (Mw = 236 Da) were 98.2%, and atenolol (Mw = 266 Da) were 99.1%.

[0093] Comparative Example 1

[0094] The only difference from Example 1 is that the number of coating layers of the high molecular weight polycation PDADMAC and the high molecular weight polyanion PSS is increased from 4 bilayers to 8 bilayers, and the number of coating layers of the low molecular weight PVAm and the low molecular weight PSS is reduced from 4 bilayers to 0 layer, and the prepared composite nanofiltration membrane contains only the high molecular weight PDADMAC / PSS system.

[0095] The test results of micro-pollutant removal rate are as follows: the pure water permeability coefficient is 19.5L m -2 h -1 bar -1 The removal rates of ibuprofen (Mw = 206 Da) were 82.7%, carbamazepine (Mw = 236 Da) were 89.3%, and atenolol (Mw = 266 Da) were 78.2%.

[0096] Comparative Example 2

[0097] The only difference from Example 1 is that the number of coating layers of the high molecular weight polycation PDADMAC and the high molecular weight polyanion PSS is reduced from 4 bilayers to 0, and the number of coating layers of the low molecular weight PVAm and the low molecular weight PSS is increased from 4 bilayers to 8 bilayers. This membrane only contains the low molecular weight PVAm / PSS system.

[0098] The test results of micro-pollutant removal rate are as follows: the pure water permeability coefficient is 4.7Lm -2 h -1 bar -1 The removal rates of ibuprofen (Mw = 206 Da) were 98.5%, carbamazepine (Mw = 236 Da) were 98.5%, and atenolol (Mw = 266 Da) were 99.3%.

[0099] The results of Example 1, Comparative Example 1 and Comparative Example 2 show that: the high molecular weight polyelectrolyte non-composite coating membrane can achieve high flux but low micro-pollutant removal rate; the low molecular weight polyelectrolyte non-composite coating membrane can achieve high micro-pollutant removal rate but low flux. The composite membrane can achieve high micro-pollutant removal rate of nanofiltration membrane by filling large pores with large molecular weight polyelectrolytes and covering small pores with small molecular weight polyelectrolytes, while ensuring high flux.

[0100] Comparative Example 3

[0101] The same base film as in Example 5 was used for polyelectrolyte coating.

[0102] A small molecular weight polyanion sodium polyacrylate (PAA, Mw = 1.5 kDa, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.) was dissolved in 0.05 mol / L sodium chloride solution to prepare a 0.1 g / L PAA polyelectrolyte solution, and then a small molecular weight polycation polyacrylamine hydrochloride (PAH, Mw = 15 kDa, purchased from Hubei Yamade Biopharmaceutical Co., Ltd.) was dissolved in 0.05 mol / L sodium chloride solution to prepare a 0.1 g / L PAH polyelectrolyte solution.

[0103] A small molecular weight polycation PAH (15 kDa) was used as the first layer. The polyethersulfone-based membrane was immersed in a PAH (15 kDa) solution for coating for 15 minutes and then washed with a 0.05 mol / L sodium chloride solution. The membrane was then immersed in a small molecular weight polyanion PAA (1.5 kDa) solution for coating for 15 minutes and then washed with a 0.05 mol / L sodium chloride solution to complete a small molecular weight system PAH / PAA polyelectrolyte double layer. The above coating steps were repeated until 10 PAH / PAA (15 kDa / 1.5 kDa) double layers were formed.

[0104] The test results of micro-pollutant removal rate are as follows: the pure water permeability coefficient is 86.5L m -2 h -1 bar -1 The removal rate of ibuprofen (Mw = 206Da) was 12.6%, the removal rate of carbamazepine (Mw = 236Da) was 17.5%, and the removal rate of atenolol (Mw = 266Da) was 26.8%. This shows that when the polyelectrolyte with too small molecular weight is coated on the base membrane with large pores, it cannot form a complete cortex and has a low removal rate for micropollutants.

[0105] Comparative Example 4

[0106] The only difference from Comparative Example 3 is that the number of PAH / PAA coating layers is increased from 10 bilayers to 20 bilayers.

[0107] The test results of micro-pollutant removal rate are as follows: the pure water permeability coefficient is 5.6Lm -2 h -1 bar -1 , the removal rate of ibuprofen (Mw = 206Da) is 97.5%, the removal rate of carbamazepine (Mw = 236Da) is 97.9%, and the removal rate of atenolol (Mw = 266Da) is 99.8%. This embodiment shows that when a polyelectrolyte with a small molecular weight is coated on a base membrane with large pores, the number of coating layers needs to be increased to form a complete cortex, but the membrane permeability coefficient is low.

[0108] Comparative Example 5

[0109] The same base film as in Example 5 was used for polyelectrolyte coating.

[0110] A high molecular weight polyanion PSS (Mw = 1000 kDa, purchased from Anhui Cool Bioengineering Co., Ltd.) was dissolved in 0.05 mol / L sodium chloride solution to prepare a 0.1 g / L PSS polyelectrolyte solution, and then a high molecular weight polycation PDADMAC (Mw = 600 kDa, purchased from Shandong Youso Chemical Technology Co., Ltd.) was dissolved in 0.05 mol / L sodium chloride solution to prepare a 0.1 g / L PDADMAC polyelectrolyte solution.

[0111] A high molecular weight polycation PDADMAC (600 kDa) was used as the first layer, and the polyethersulfone-based membrane was immersed in a PDADMAC (600 kDa) solution for coating for 15 minutes and then washed with a 0.05 mol / L sodium chloride solution. The membrane was then immersed in a high molecular weight polyanion PSS (1000 kDa) solution for coating for 15 minutes and then washed with a 0.05 mol / L sodium chloride solution to complete a high molecular weight system PDADMAC / PSS polyelectrolyte double layer. The above coating steps were repeated until 10 PDADMAC / PSS (600 kDa / 1000 kDa) double layers were formed.

[0112] The test results of micro-pollutant removal rate are as follows: the pure water permeability coefficient is 28.2L m -2 h -1 bar -1 The removal rates of ibuprofen (Mw = 206Da) were 56.2%, carbamazepine (Mw = 236Da) were 72.0%, and atenolol (Mw = 266Da) were 78.1%. This indicates that a high-flux nanofiltration membrane can be obtained with a large molecular weight polyelectrolyte coating and a large-pore base membrane, but the removal rate of micropollutants is low.

[0113] Comparative Example 6

[0114] The only difference from Comparative Example 5 is that the number of PDADMAC / PSS coating layers is increased from 10 bilayers to 20 bilayers.

[0115] The test results of micro-pollutant removal rate are as follows: the pure water permeability coefficient is 19.2L m -2 h -1 bar -1 , the removal rate of ibuprofen (Mw = 206Da) was 62.7%, the removal rate of carbamazepine (Mw = 236Da) was 75.8%, and the removal rate of atenolol (Mw = 266Da) was 81.4%. This shows that even if the number of coating layers is increased, the base membrane with large molecular weight polyelectrolyte coating and large pores cannot achieve a high micropollutant removal rate.

[0116] The results of Example 5 and Comparative Examples 3, 4, 5, and 6 show that when coating on a macroporous base membrane, more layers of small molecular weight polyelectrolytes are required to obtain a defect-free nanofiltration membrane but the flux is low. When coating with a large molecular weight polyelectrolyte, a lower number of layers can obtain a defect-free nanofiltration membrane but the removal rate of micropollutants is low. The defect-free nanofiltration membrane obtained by filling the large pores with a large molecular weight polyelectrolyte system and the small pores with a small molecular weight polyelectrolyte system can achieve a high removal rate for micropollutants while ensuring a high water flux.

[0117] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a composite nanofiltration membrane, characterized in that: The following steps are involved: Using the dip coating method, (1) Alternately coating high molecular weight polyelectrolyte solutions with opposite charges on a base film, and repeating the alternate coating to a desired number of layers to obtain a macroporous filled polyelectrolyte multilayer film; (2) alternately coating small molecular weight polyelectrolyte solutions with opposite charges on the macroporous filling polyelectrolyte multilayer membrane, and repeating the alternate coating until a desired number of polyelectrolyte multilayer membranes are formed to obtain a composite nanofiltration membrane; The molecular weight of the high molecular weight polyelectrolyte in the high molecular weight polyelectrolyte solution is 200 to 3000 kDa; The molecular weight of the small molecular weight polyelectrolyte in the small molecular weight polyelectrolyte solution is 1 to 200 kDa.

2. The preparation method according to claim 1, characterized in that: The porosity of the base membrane is 50-80%, and the pore size is 10-200 nm; the material of the base membrane includes polyethersulfone, polyacrylonitrile, polysulfone, polyetheretherketone, polyimide or polyvinyl chloride, and the type of the base membrane is a hollow fiber membrane.

3. The preparation method according to claim 1, characterized in that: The large molecular weight polyelectrolyte and the small molecular weight polyelectrolyte independently include polycation electrolytes or polyanion electrolytes.

4. The preparation method according to claim 3, characterized in that: The polycation electrolyte comprises one or more of polyacrylamine hydrochloride, polydimethyldiallylammonium chloride, polyethyleneimine and polyethyleneamine; The polyanion electrolyte includes one or more of sodium polystyrene sulfonate, sodium polyacrylate, sodium polyvinyl sulfonate and sulfonated polyetheretherketone.

5. The preparation method according to claim 1 or 4, characterized in that: The concentration of polyelectrolyte in the large molecular weight polyelectrolyte solution and the small molecular weight polyelectrolyte solution is 0.01-10 g / L.

6. The preparation method according to claim 1, characterized in that: The salt in the background salt solution used for the high molecular weight polyelectrolyte solution and the low molecular weight polyelectrolyte solution independently includes NaF, NaCl, NaBr or NaNO3, and the salt concentration in the background salt solution is 0.0001-2.5 mol / L.

7. The preparation method according to claim 1, characterized in that: Based on the fact that one double layer is obtained by alternating coating once, the number of layers of alternating coating in step (1) is 2 to 10 double layers; the number of layers of alternating coating in step (2) is 1 to 10 double layers.

8. The preparation method according to claim 1 or 7, characterized in that: The order of alternating coating in step (1) and step (2) is independent of sequential coating of polycationic electrolyte and polyanionic electrolyte.

9. The composite nanofiltration membrane prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the composite nanofiltration membrane according to claim 9 in the treatment of drinking water or surface water.

Citation Information

Patent Citations

  • Inorganic / organic composite nanofiltration membrane and preparation method thereof

    CN102553461A

  • Method for producing polyelectrolyte self-assembly composite nanofiltration membrane

    CN102580550B

  • A method for preparing nanofiltration membranes by layer-by-layer self-assembly

    CN105169962B

  • Preparation method of composite nano-filtration membrane with self-repairing, bacterium-resisting and solvent-resisting functions

    CN106310975A

  • Layer-by-layer self-assembled polydopamine amphoteric composite nanofiltration membrane and preparation method thereof

    CN107519765A